Exploring The Dynamics Of Multidisciplinary Healthcare Teams: Insights From Doctors And Nurses. A New Approach (Journal of Namibian Studies : History Politics Culture, 2022)
Multidisciplinary healthcare teams play a crucial role in delivering comprehensive and patient-centered care. This article delves into the dynamics of these teams, focusing on insights from both doctors and nurses. By examining the perspectives, challenges, and strategies of healthcare professionals involved in interdisciplinary collaboration, this study seeks to enhance our understanding of effective teamwork within healthcare settings. Insights from doctors and nurses provide valuable perspectives on communication, role clarity, mutual respect, and shared decision-making, shedding light on the key factors influencing the dynamics of multidisciplinary teams.